DIAGNOSIS DAN PENATALAKSANAAN ARTRITIS SEPTIK - Dary, I Wayan; Raka Putra, Tjokorda (journal of internal medicine, 2012)
Septic arthritis which caused by bacterial infection is a serious disease and still as challenge to physician because the prognosis has not improved significantly over the past two decades. The route of spread infection to joint through hematogenous or other routes include direct inoculation through joint prosthetic. The most often aetiology is Staphylococcus aureus. The process of native joint infection can be divided into three steps: bacterial colonization, establishing an infection, and induction of host inflammatory response. The diagnosis of septic arthritis rests on isolation of the pathogen from joint fluid. If we find classic sign and symptoms associated septic arthritis should not to delay the diagnosis of septic arthritis. Once septic arthritis is suspected and the proper sample for microbiologic studies are collected, appropriate antibiotic treatment and adequate joint drainage should begin immediately. The aim management of septic arthritis mainly are joint decompression, joint sterilization, and reserve joint function. Sterilization joint with empirical antibiotic based on gram stain and co-morbid disease and than adjusted base on baterial culture result. Antibiotic should be administrated intravenously at least 2 weeks than continued orally. Joint decompression can be achieved by a variety methods include closed-needle aspiration, tidal irrigation, arthroscopy, and arthrotomy. Prophylactic use of antibiotics is controversial for events posing a risk of haematogenous bacterial arthritis through transient bacteraemia. Prognosis of septic arthritis is poor since a permanent reduction in joint function is seen in approximately 30% of patients.
Keywords: septic arthritis, diagnosis, management